Pre-admission tests of learning potential as predictors of academic success of first-year medical students - Wadee, A A; Cliff, A (South African Journal of Higher Education, 2016)
Whilst performance in the school-leaving examination may be a good predictor of academic achievement at medical schools, it is not necessarily a perfect one. The Health Sciences Placement Tests (HSPTs), comprising four components, were adopted by several South African universities as a tool to understand student preparedness. Of 127 first-year students at the University of the Witwatersrand in 2010, those from private schools performed significantly better academically than their public school counterparts on overall HSPT performance and in the Academic Language test, and marginally better in the Mathematics Achievement and Mathematics Comprehension tests. Students from private schools performed better at first-year level in the subjects of Psychology and Fundamentals of Medical and Clinical Sciences. The Academic Language and Mathematics Comprehension tests showed significant correlations with performance in first-year subjects, both at mid-year and year-end assessments. The study points to the importance of the HSPTs as an additional tool in predicting and understanding academic success at first-year university level.